Menenangkan Hati Remaja dengan Tazkiyatun Nafs: Terapi Spiritual untuk Membersihkan dan Menenangkan Hati Remaja Desa Jumputrejo, Sidoarjo - Fikril Hidayat, Moch Calvin (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 25 No 1 (2025), 2025)
This journal discusses the importance of tazkiyatun nafs as a spiritual therapy to calm the hearts of adolescents. Tazkiyatun nafs, which means purification of the soul, serves to cleanse oneself of negative traits and strengthen faith. This research used a qualitative method with a literature study case of adolescent in Desa Jumputrejo, Sidoarjo related to tazkiyatun nafs, its impact on adolescent mental health, and relevant spiritual practices. The results showed that tazkiyatun nafs can help adolescents overcome various psychological problems such as anxiety, stress and internal conflicts. By internalizing the values of tazkiyah, adolescents can achieve inner peace, improve moral quality, and build harmonious social relationships. The findings suggest that the application of tazkiyatun nafs in daily life is essential to support adolescents' spiritual and emotional development, so that they can live happier and more meaningful lives. This journal is expected to contribute to further research on spiritual interventions in the context of adolescent mental health.